Guiding pancreatic beta cells to target electrodes in a whole-cell biosensor for diabetes1. Issue 19 (7th October 2015) - Pedraza, Eileen; Karajić, Aleksandar; Raoux, Matthieu; Perrier, Romain; Pirog, Antoine; Lebreton, Fanny; Arbault, Stéphane; Gaitan, Julien; Renaud, Sylvie; Kuhn, Alexander; Lang, Jochen
<x xml:space="preserve">Abstract</x> We present a method for delivering cells to target electrodes of a whole-cell bioelectronic sensor for multi-parametric sensing of glucose and physiological hormone regulators.